Racial and ethnic differences in end-of-life care in the United States: Evidence from the Health and Retirement Study (HRS) - Orlovic, Martina; Smith, Katharine; Mossialos, Elias (SSM - population health, 2019)
Population ageing poses considerable challenges to the provision of quality end-of-life care. The population of the United States is increasingly diverse, making it imperative to design culturally sensitive end-of-life care interventions. We examined participants of the Health and Retirement Study, who died between 2002 and 2014, to examine racial and ethnic differences in end-of-life care utilization and end-of-life planning in the United States. Our study reveals significant disparities in end-of-life care and planning among studied groups. Findings reveal that racial and ethnic minorities are more likely to die in hospital and less likely to engage in end-of-life planning activities. The observed disparities are still significant but have been narrowing between 2002 and 2014. Efforts to reduce these differences should target both medical professionals and diverse communities to ensure that improved models of care acknowledge heterogeneous values and needs of a culturally diverse US population.